1989
DOI: 10.1115/1.3257089
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a Hovercraft Air Cavity Under a Floating Ice Sheet

Abstract: An ACIB is an air cushion device being developed in Canada for icebreaking purposes. When mated with the bow of a tugboat, the ACIB currently operational can break ice sheets about 1 m thick. During ACIB operations, the water surface directly beneath the craft is sometimes depressed below the lower edge of the ice sheet, and an air cavity is formed under the sheet. This air cavity is known to have a significant effect on the icebreaking capability of the ACIB. In a study for Transport Canada, DeHavilland Aircr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, when d is less than 0.9 hi, the air cavity cannot be formed under the ice sheet. In Hinchey's [3] experiment, he observed that the air cavity radiates out in a semicircular shape under the ice sheet. Without considering the air leakage, the relationship between the radius and height of the air cavity is written as:…”
Section: Ship-ice Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when d is less than 0.9 hi, the air cavity cannot be formed under the ice sheet. In Hinchey's [3] experiment, he observed that the air cavity radiates out in a semicircular shape under the ice sheet. Without considering the air leakage, the relationship between the radius and height of the air cavity is written as:…”
Section: Ship-ice Mathematical Modelmentioning
confidence: 99%
“…Hinchey et al [1] conducted a model test of hovercraft breaking ice at low speed and analyzed corresponding ice resistance. Hinchey [3] carried out model tests and believed that the theory of gravity currents was more consistent with reality. Lu et al [4,5] analyzed the ice-breaking mechanism of hovercraft at high speed and came up with the critical speed.…”
Section: Introductionmentioning
confidence: 99%